Virology on the Internet: the time is right for a new journal - Garry, Robert F (BioMed Central, 2004)
Virology Journal is an exclusively on-line, Open Access journal devoted to the presentation of high-quality original research concerning human, animal, plant, insect bacterial, and fungal viruses. Virology Journal will establish a strategic alternative to the traditional virology communication process.